Application Development wtih Service Oriented Architecture - Rıdvan SARAÇOĞLU; Emine DOĞAÇ (International Journal of Applied Methods in Electronics and Computers, 2019)
Today, it is one of the most invested areas of organizations to ensure the interoperability of existing corporate applications and newly developed or purchased applications. Developed systems are designed to be shaped according to the needs of the businesses that use it. Classical systems are automation systems that operate from point to point and from other platforms in the enterprise without interaction. Unlike these, the service-oriented architecture (SOA) contains a structure that is ready to interact. In this study, a system has been designed in order to reduce the integration costs between the applications in the long term by using SOA approach, to shorten the business processes in the institution and to reduce the economic costs. In the project, work pieces were published as a method of service over the service layer. Thus, the platform independent main application is accessible to each work piece. At the same time, these work pieces can come together and be reconfigured according to the request of the enterprise. Some of the advantages achieved by using SOA are: Providing improved work processes for services and actors, ensuring collaboration, utilizing from existing and reuse with savings, providing business flexibility by responding to changing business needs.